SPECIES IDENTIFICATION AND GENETIC DIVERSITY OF PORTUGUESE OYSTER (Crassostrea angulata): IMPLICATIONS FOR BREEDING IN VIETNAM - Nguyen, Luan Thanh; Nguyen, Thong Hoang; Nguyen, Loc Hong; Le, Nguyen Hoang Khoi; Nguyen, Suong Thao; Nguyen, Thanh Minh; Nguyen, Tri Nhu; Nguyen, Sang Van (Indonesian Aquaculture Journal, 2025)
Cupped oyster has emerged as the predominant mollusk farmed domestically in Vietnam because of its exceptional adaptability to the local subtropical and tropical climates. However, considerable confusion remains regarding the identity of the cultivated species due to the taxonomic ambiguity between Portuguese cupped oyster (Crassostrea angulata) and Pacific cupped oyster (Crassostrea gigas). This study aims to clarify the species identity of the most commonly farmed cupped oysters in Vietnam and to evaluate genetic diversity and the suitability of oyster strains for a breeding program including three Vietnamese strains (Quang Ninh, Khanh Hoa, and Vung Tau) and one wild population from Taiwan. Based on mitochondrial DNA cytochrome c oxidase subunit I (COI) sequences, our results confirmed that all samples in Vietnam and Taiwan are C. angulata. Furthermore, this study performed genetic analyses using mtCOI sequences and five microsatellites. Populations in Vietnam and Taiwan maintain high levels of genetic diversity, with the average number of alleles per population varied between 7.80 to 16.0, and there was no statistical difference between observed and expected heterozygosity (P > 0.05), except in the hatchery population Vung Tau. The samples collected from this population suffered a great loss of heterozygosity and occupied the highest Fis value (Fis = 0.3), which is likely due to the small size of founding stock and long-term artificial breeding by local hatchery farmers, resulting in a strong genetic bottleneck and inbreeding depression. Pairwise FST calculated by microsatellites with a range of 0.043 to 0.093 revealed significant (P < 0.05) levels of genetic differentiation among oyster lines. Collectively,  our findings clarify the taxonomic status of farmed oysters in Vietnam and highlight the importance of crossing among different strains in future breeding programs to maximize the genetic gain and avoid inbreeding, especially when using the oyster strain from Vung Tau.